2023
DOI: 10.1038/s41598-023-29676-9
|View full text |Cite
|
Sign up to set email alerts
|

First principles and mean field study on the magnetocaloric effect of YFe3 and HoFe3 compounds

Abstract: In this work, the magnetothermal characteristics and magnetocaloric effect in YFe3 and HoFe3 compounds are calculated as function of temperature and magnetic field. These properties were investigated using the two-sublattice mean field model and the first-principles DFT calculation using the WIEN2k code. The two-sublattice model of the mean-field theory was used to calculate the temperature and field-dependences of magnetization, magnetic heat capacity, magnetic entropy, and the isothermal change in entropy ∆S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…For example, Simmons et al [6 ] focuses on the neutron and x-ray diffraction on HoFe3 and YFe3 compounds. In fact, some of the present authors have recently reported on ab initio calculation of the elastic properties and on magnetothermal and magnetocaloric effect in these same compounds [ 7 ], also Matsuda et al [ 8] reported also on the crystallographic properties and on the magnetic moments at 4.2 K only.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…For example, Simmons et al [6 ] focuses on the neutron and x-ray diffraction on HoFe3 and YFe3 compounds. In fact, some of the present authors have recently reported on ab initio calculation of the elastic properties and on magnetothermal and magnetocaloric effect in these same compounds [ 7 ], also Matsuda et al [ 8] reported also on the crystallographic properties and on the magnetic moments at 4.2 K only.…”
Section: Introductionsupporting
confidence: 50%
“…The MFT has been used in studies on other rare-earth transition metal compounds e.g. YFe3 and HoFe3 [7], TmFe2 [9], R2Fe14B [10], ErFe2 [11], R3Co11B4 [12] and R6Fe23 [13]. In the present work we present a theoretical study on MCE (∆Sm , ∆Tad) of DyFe3 and GdFe3 using the MFT.…”
Section: Introductionmentioning
confidence: 99%